2018
DOI: 10.1038/s41564-018-0229-0
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy proteins suppress protective type I interferon signalling in response to the murine gut microbiota

Abstract: As a conserved pathway that lies at the intersection between host defence and cellular homeostasis, autophagy serves as a rheostat for immune reactions. In particular, autophagy suppresses excess type I interferon (IFN-I) production in response to viral nucleic acids. It is unknown how this function of autophagy relates to the intestinal barrier where host-microbe interactions are pervasive and perpetual. Here, we demonstrate that mice deficient in autophagy proteins are protected from the intestinal bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 56 publications
1
61
0
Order By: Relevance
“…Moreover, cytoplasmic lysozyme levels were reduced and protective molecules, such as MUC2, were highly expressed by goblet cells, an indication of the altered inner intestinal layer resulting from overactivated immune response in the absence of ATG. 38,46 From previous studies, the absence of autophagy increased the inflammatory response, essentially altering the microbiome and intestinal layer; 40,48 however, this is yet to be demonstrated in the airway microbiota-Mtb interaction.…”
Section: Immunity (Autophagy)-microbiome Interactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, cytoplasmic lysozyme levels were reduced and protective molecules, such as MUC2, were highly expressed by goblet cells, an indication of the altered inner intestinal layer resulting from overactivated immune response in the absence of ATG. 38,46 From previous studies, the absence of autophagy increased the inflammatory response, essentially altering the microbiome and intestinal layer; 40,48 however, this is yet to be demonstrated in the airway microbiota-Mtb interaction.…”
Section: Immunity (Autophagy)-microbiome Interactionsmentioning
confidence: 98%
“…In the case of C. rodentium, autophagycompetent monocytes attracted to the infection site aided in the resolution of the infection. 48 In effect, autophagy influences the composition of the intestinal microbiota through IFN-I inhibition.…”
Section: Immunity (Autophagy)-microbiome Interactionsmentioning
confidence: 99%
“…However, other studies have reported that autophagy deficiency increases resistance to infection with C. rodentium [80,81]. Marchiando et al reported that compared to WT mice, Atg16l1[HM] mice are more resistant to C. rodentium infection, displayed by reduced number of C. rodentium associated to the colon and caecum, increased survival, decreased weight loss and diarrheal disease and protection from colonic inflammation [80].…”
Section: Autophagy and Innate And Adaptive Immune Responsesmentioning
confidence: 99%
“…In addition, Atg16L1-hypomorphic mice developed intestinal abnormalities resembling CD whilst displaying resistance to intestinal infection with the bacterium Citrobacter rodentium 45,46 . Published findings suggest that autophagy may serve as a rheostat for immune reactions 47 . These opposite effects in Buruli ulcer and CD provide another example of mirror genetic effects (i.e.…”
Section: Discussionmentioning
confidence: 99%